THU0466-HPR Maintenance of physical activity in patients with rheumatoid arthritis: A qualitative interview study. (23rd January 2014) - Loeppenthin, K.; Esbensen, B.A.; Thomsen, T.; Midtgaard, J.
Abstract : Background: Several exercise trials indicate that physical activity (PA) may improve physical function and quality of life, and reduce pain in patients with rheumatoid arthritis (RA). 1, 2 Few of these studies have included physical activity maintenance. Thus, it is still unknown how and why some patients with RA are able to maintain physical active. Objectives: The aim of this study was to describe the experience of physical activity maintenance in patients with RA. Methods: A qualitative salutogenetic-oriented study was conducted based on individual semi-structured interviews. Interviewee selection was carried out through purposeful sampling. On this basis, participants with self-reported regular physical activity were invited to participate in the study. In total, 16 individuals (12 women and four men; mean age 50), diagnosed with RA for an average of 21 years (range: 4–46 years) and with variation in functional ability participated in the study. The participants were recruited from an outpatient clinic. The recorded interviews were transcribed verbatim and was analysed by use of NVivo software trough systematic text condensation inspired by Giorgi's phenomenological methodology. 3 The analysis was discussed within a multidisciplinary team of qualitative researchers. Results: The analysis revealed tree dimensions of PA maintenance: (1) A bodily dimension: physical sensations of vitality, sparkling energy and liberation in movement; (2) a mental component: referring to experiences of self-determination, pride and success; and (3) a social component: containing feelings of independency and a sense of community. The essence of the tree dimensions was to strive for transparency' understood as the experience of the body as a whole . Furthermore, PA maintenance was described as a resistance resource allowing the participants to adjust to the uncertainty of the illness and preserving hope for a future dominated as little as possible by illness. Conclusions: While RA usually forces a negative attention to joint pain, fatigue and limited mobility in parts of the body, the participants in this study, despite illness, described experiences of bodily well-being and liberation from illness provided and secured through PA maintenance. The understanding of regular PA as a resistance resource is essential to development future health promoting interventions aimed to encourage PA maintenance in patients with RA. References: Hurkmans E, van der Giesen FJ, Vliet Vlieland TP, Schooned J, Van den Ende EC. Dynamic exercise programs (aerobic capacity and/or muscle strength training) in patients with rheumatoid arthritis. Cochrane Database Syst Rev. 2009 Oct 7;(4):CD006853 Cairns AP, McVeigh JG. A systematic reivew of the effects of dynamic exercise in rheumatoid arthritis. Rheumatol Int. 2009 Dec; 30(2):147-58 Giorgi A. A phenomenological perspective on certain qualitative research methods. J Phenomenol Psychol. 1994; 25: 190-220 Disclosure of Interest: None Declared